The Impact of Anthropomorphism on Purchase Intention of Smartphones : A Study of Young Indian Consumers - Gupta, Ritu; Jain, Kokil (Indian Journal of Marketing, 2019)
The purpose of this study was to explore the role of anthropomorphism in influencing the consumers’ purchase intentions in the case of smartphones. The study employed between the group experimental design to check the proposed hypotheses on young smartphone users between the age group of 18 - 25 years. A hypothetical brand â€œUSENâ€ was created. Two versions of the ad - anthropomorphic and non - anthropomorphic were developed for the hypothetical brand. Multivariate analysis of variance (MANOVA) technique using SPSS Version 23 was used to test the results. The results established a significant positive differential effect of the anthropomorphic ad over the non - anthropomorphized version of the advertisement on consumers’ feelings, attitude towards the ad, attitude towards the brand, and purchase intention. The research holds valuable contribution for companies to effectively utilize the concept of anthropomorphism to develop a favourable attitude towards their brands.